PREJUDICE AND COMMUNICATION ETHICS AS CONFLICT’S RESOLUTION (PEMBACAAN M. QURAISH SHIHAB TERHADAP QS AL-HUJURAT 11-12) - Adon Jubaidi (Jurnal Dakwah Tabligh, 2019)
This paper discussed Prejudice and Communication Ethics as Conflict Resolution in Indonesia. It will explore both Muhammad Quraish Shihab and his interpretation of Quran Sura Al-Hujurat: 11-12. Muhammad Quraish Shihab is one of Mufassir in Indonesia. Most of the conflicts had occurred because of the wrong and negative prejudice about someone or specific community. It has happened in Indonesia. There are many conflicts that reasons are simple. But, it had a big effect because of misscommunication and negative prejudice. Moreover, conflicts are in social media. So, the Quran has the solution to it. In Quran Sura al-Hujurat: 11-12, tell us about Ethics of Communication and Prejudice, that was explained by Muhammad Quraish Shihab in his Tafsir, Al-Misbah.